2018
DOI: 10.1111/nep.13050
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir‐based treatment is safe and effective in Indian hepatitis C patients on maintenance haemodialysis: A retrospective study

Abstract: Our study demonstrates that sofosbuvir-based therapy is efficacious for HCV viraemia in patients on maintenance haemodialysis. The therapy was found to be reasonably safe with no major adverse effects noted with the use of sofosbuvir, ledipasvir or daclatasvir. However, larger studies are needed to validate our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…In studies where both SVR4 and SVR 12 rates were reported, SVR4 rate was seldomly less than SVR12 rate. 1,6,10,12,13,18,19,28,29 The same applies to SVR24 rate, which was also lower than SVR12 rate in pooled analysis and had been reported only in five studies. 10,12,14,20,24 Besides, long-term virologic response might be affected by genotype, regimen or the interactions between these two factors.…”
Section: Discussionmentioning
confidence: 83%
“…In studies where both SVR4 and SVR 12 rates were reported, SVR4 rate was seldomly less than SVR12 rate. 1,6,10,12,13,18,19,28,29 The same applies to SVR24 rate, which was also lower than SVR12 rate in pooled analysis and had been reported only in five studies. 10,12,14,20,24 Besides, long-term virologic response might be affected by genotype, regimen or the interactions between these two factors.…”
Section: Discussionmentioning
confidence: 83%
“…The included studies were published from 2015 to 2020 and contained extractable data on 514 patients enrolled from 2014 to 2016. Four studies were retrospective [10][11][12][13] and 16 were prospective [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Nine of the studies were conducted in India 10,12,14,16,18,20,22,25,29 , 2 in the USA 15,21 , 2 in Pakistan 24,28 , 2 in China 19,27 , 1 in France 17 , the Czech Republic 11 , Korea 13 , Iraq 26 , and 1 enrolled patients from multiple countries 23 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 19 studies reported extractable data on the SOF dose [10][11][12][13][14][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and the other DAA included in the treatment regimen. In nine studies [10][11][12][13]16,19,[21][22][23] , the same treatment regimen was used for all study participants. Six studies partitioned the study participants into subgroups and followed a different treatment strategy for each subgroup 14,17,18,20,24,25 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations